1992
DOI: 10.1002/jemt.1070230405
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopy of Golgi‐impregnated interneurons: Notes on the intrinsic connectivity of the cerebral cortex

Abstract: The Golgi‐electron microscope technique has opened new avenues to explore the synaptic organization of the brain. In this article, we shall discuss basic methodological principles necessary to analyze axonal arborizations with this combined technique. To illustrate the applications of the method, we shall review the forms and distribution of the synapses in which the axonal arborizations of local cortical interneurons engage. © 1992 Wiley‐Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…In general terms, these studies showed that some nonpyramidal neurons, such as the multipolar and bitufted cells, form symmetric synapses with the cell bodies and dendritic shafts of both pyramidal and nonpyramidal neurons (e.g., LeVay, 1973;Peters and Fairén, 1978;Peters and Proskauer, 1980;Fairén and Smith-Fernández. 1992), while the basket cells prefer to synapse on the cell bodies and proximal dendrites of pyramidal and non-pyramidal cells (e.g.…”
Section: Golgi Electron Microscopymentioning
confidence: 99%
“…In general terms, these studies showed that some nonpyramidal neurons, such as the multipolar and bitufted cells, form symmetric synapses with the cell bodies and dendritic shafts of both pyramidal and nonpyramidal neurons (e.g., LeVay, 1973;Peters and Fairén, 1978;Peters and Proskauer, 1980;Fairén and Smith-Fernández. 1992), while the basket cells prefer to synapse on the cell bodies and proximal dendrites of pyramidal and non-pyramidal cells (e.g.…”
Section: Golgi Electron Microscopymentioning
confidence: 99%